2008
DOI: 10.1021/jp077367b
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Excited States in Jet-Cooled Aromatic Molecules:  Bifurcating Pathways and Very Long Lived Species from the S1 Excitation of Phenylacetylene and Benzonitrile

Abstract: Pump-probe delayed ionization studies on phenylacetylene and benzonitrile in a supersonic beam reveal the production of a low-ionization-potential (approximately 5.7 eV) species lasting more than hundreds of microseconds after excitation to the S1 state. Excitation of the molecules was done with a frequency-doubled, Fourier transform-limited, pulse-amplified cw laser, and the rotationally resolved structure of the S1-S0 transition ensures that the excited molecules are monomers. Excited-state photoelectron spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…To begin with, all the six (fluoro)phenylacetylenes considered in the present investigation are fluorescent following excitation to 1 ππ* (S 1 ) state. [17] Any singlet dark state that can couple and possibly quench the fluorescence is not energetically accessible, at least from the Frank-Condon zone (Figure7, top panel). This description also holds for all the complexes with intermolecular structures that do not involve � CÀ H•••X hydrogen bonding with the acetylenic group, such as structures M1, M3 ( Figure 2) and C1, C9 (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To begin with, all the six (fluoro)phenylacetylenes considered in the present investigation are fluorescent following excitation to 1 ππ* (S 1 ) state. [17] Any singlet dark state that can couple and possibly quench the fluorescence is not energetically accessible, at least from the Frank-Condon zone (Figure7, top panel). This description also holds for all the complexes with intermolecular structures that do not involve � CÀ H•••X hydrogen bonding with the acetylenic group, such as structures M1, M3 ( Figure 2) and C1, C9 (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, an increase in the CÀ H•••X hydrogen bond strength moves the dark state away from the Franck-Condon region thereby switching ON the fluorescence emission (see lower panel in Figure 7). Further, the excited state lifetime of the monomers viz., PHA (70 ns), [17] 2FPHA (84 ns), 3FPHA (76 ns), 4FPHA (90 ns) and 26DFPHA (63 ns) are in the range of 63-90 ns, and those of fluorescent complexes are much lower and are within the laser pulse width of about 8 ns, therefore could not be measured accurately with ns laser. On the other hand, the lifetimes of the non-fluorescent complexes are expected to be much lower than the fluorescent complexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, in our laboratory it was found that phenylacetylene and benzonitrile pumped by nanosecond lasers did not follow a classical kinetic scheme at all. 15,16 Their triplet states were entirely populated during the laser pulse--only--and then the triplet populations did not decay at all during the 140 μs we could observe them in the beam. This is completely inexplicable in the generally accepted model of the way larger isolated molecules are supposed to behave.…”
Section: Introductionmentioning
confidence: 85%
“…Since they thought that none of the standard processes (IC, ISC or IVR) were responsible, this unknown phenomenon was named "channel three" and remained mysterious for a long time. [32][33][34][35] In previous work, we investigated the low vibronic S 1 state of o-xylene with one-photon pump at 266 nm. The lifetime of the low vibronic S 1 state with vibronic energy of 0.02 eV is much longer, extrapolated to ∼12.7 ns.…”
Section: Time-resolved Fragment-ion Imagingmentioning
confidence: 99%